Enhanced NF-κB signaling in type-2 dendritic cells at baseline predicts non-response to adalimumab in psoriasis - Rosa Andres-Ejarque (Nature Portfolio, 2021)
Biomarkers to indicate potential response to biologic therapeutics are needed for patients with psoriasis. Here the authors show that phosphorylation of NFκBp65 in cDC2 before therapy is an indication of non-response to the anti-TNF therapy adalimumab in patients with psoriasis.